Marketing Communication in International Relations - Sharazani Velayati (Program Studi Hubungan Internasional FISIP Universitas Jayabaya, 2022)
The goal of this article is discuss the connection between marketing communication and the discipline of international relations. Basically International Relations is learning about global issues, social science and global policy. Marketing communication is adapting our message so that it fits the desired market. For marketers, having a solid understanding of global issues, policies and cultures is a necessity for marketing communication. Marketing communication,’ international trade, globalization, the liberal-capitalist world order — however we want to refer to international economic relations — clearly ties states together